Cloud-based mobile service provisioning for system performance optimisation. (2018) - Chunlin, Li; Jing, Zhang; Youlong, Luo
Currently, the mobile applications require intensive computational resources, particularly CPUs, RAMs, storage and battery to successfully complete the expected computing operation. Although distant clouds feature high availability and elastic scalability, and performance gain of utilising such resources is decreased by high communication latency due to large number of intermediate hops between the mobile device and the distant public clouds. Therefore, local cloud is suitable choice for some mobile devices. In this paper, hybrid cloud-assisted mobile service optimisation model is proposed to tackle limited resources of mobile devices and enhance the overall system performance. The aim of hybrid cloud-assisted mobile service optimisation is that mobile cloud system utility is optimised while satisfying huge number of mobile requests and improving individual user's quality of service (QoS) and reducing system overheads. The hybrid cloud-assisted mobile service scheduling algorithm enables mobile applications conducted on mobile devices to complete all tasks by leveraging computing resources of public cloud and local cloud. The proposed algorithm is validated through a series of experiments.